2022
DOI: 10.3390/nu14193918
|View full text |Cite
|
Sign up to set email alerts
|

Oral Erythritol Reduces Energy Intake during a Subsequent ad libitum Test Meal: A Randomized, Controlled, Crossover Trial in Healthy Humans

Abstract: The impact of oral erythritol on subsequent energy intake is unknown. The aim was to assess the effect of oral erythritol compared to sucrose, sucralose, or tap water on energy intake during a subsequent ad libitum test meal and to examine the release of cholecystokinin (CCK) in response to these substances. In this randomized, crossover trial, 20 healthy volunteers received 50 g erythritol, 33.5 g sucrose, or 0.0558 g sucralose dissolved in tap water, or tap water as an oral preload in four different sessions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Similar results have been observed for erythritol. Acute intragastric or oral administration of varying doses (10 to 75 g in 300 mL water) of erythritol induced the secretion of GLP-1, CCK, and PYY, but not GIP [ 34 , 35 , 36 , 37 , 38 ]. Teysseire et al [ 39 ] found a decrease in plasma ghrelin concentrations in response to an intragastric administration of 50 g of erythritol in 300 mL water, compared to D-allulose and water, in healthy, normal-weight individuals.…”
Section: Effects On Gastrointestinal Hormonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results have been observed for erythritol. Acute intragastric or oral administration of varying doses (10 to 75 g in 300 mL water) of erythritol induced the secretion of GLP-1, CCK, and PYY, but not GIP [ 34 , 35 , 36 , 37 , 38 ]. Teysseire et al [ 39 ] found a decrease in plasma ghrelin concentrations in response to an intragastric administration of 50 g of erythritol in 300 mL water, compared to D-allulose and water, in healthy, normal-weight individuals.…”
Section: Effects On Gastrointestinal Hormonesmentioning
confidence: 99%
“…In a study by Teysseire et al [ 37 ], the administration of a pure oral erythritol (50 g in 300 mL water) preload translated into a reduction in subsequent energy intake during an ad libitum test meal, but also into a reduction in total energy intake, compared to other preloads containing sucrose (33.5 g), sucralose (55.8 mg), or water in healthy, normal-weight individuals.…”
Section: Effects On Energy Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Although the effects of erythritol on gut hormone secretion and gastric emptying remain inconclusive [19], certain studies have indicated that erythritol may elicit different responses compared to other sweeteners such as xylitol [20]. In a randomized, controlled crossover trial, erythritol was found to reduce energy intake during a subsequent ad libitum test meal in healthy participants [21]. Furthermore, erythritol and xylitol have been reported to differentially impact brain networks involved in appetite regulation, potentially suggesting distinct mechanisms underlying their effects on satiety [22].…”
Section: The Use Of Erythritol In Obesitymentioning
confidence: 99%
“…2,6,7 Many specic experiments have proved that erythritol is a safe food additive without toxicity, carcinogenicity and chromosomal damage. [8][9][10][11] Erythritol has gradually become attractive to assist people with obesity and diabetes with weight management and blood glucose control. However, the price of low-calorie sweeteners is much higher than that of traditional sugars due to the market share and production cost.…”
Section: Introductionmentioning
confidence: 99%